Re-Excavation of Kansyore Island - Kyazike, Elizabeth (My University, 2019)
This paper contributes to a better understanding of the archaeology of Kansyore Island and the Kansyore phenomenon at the type site. The Kansyore site has abundant and highly decorated ceramics of Neolithic and Early Iron Age traditions. The Neolithic pottery are similar to those which have been identified in several other places, such as southern Sudan. Theories such as migration, and diffusion have been used to explain this cultural similarity or affinity, basing on pottery decorations. This paper goes beyond pottery decoration to show that cultural affinity existed at Kansyore during the Neolithic period. Accumulated data from field survey and excavation suggest for the existence of roulette in the Neolithic context, which implies that pottery traditions cannot be associated with ethnicities. The association of pottery traditions of different cultural periods like Urewe and Kansyore need parsimonious explanation than just being associated with post deposition disturbance.
Keywords: Kansyore; cultural interactions; cultural affinity